2019
DOI: 10.1111/jace.16955
|View full text |Cite
|
Sign up to set email alerts
|

Tunable microwave dielectric properties in SrO‐V2O5 system through compositional modulation

Abstract: Adjustment on resonance frequency stability against the sintering temperature of Sr3V2O8 was realized by adjusting the Sr:V mole ratio. Effects of Sr:V ratio on sintering behavior and dielectric properties of Sr3V2O8 were studied. The sintering temperature was sucessfully reduced to 950°C from 1150°C. With increasing vanadium content, both relative permittivity and quality factor decreased, while the temperature coefficient of resonance frequency shifted from positive to negative values. Especially, a near‐zer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 30 publications
0
20
0
Order By: Relevance
“…5. The apparent densities of the major sample was an approximate value of 3.80 g/cm 3 and relative density also has reached more than 95%. It is noticeable that the good degree of densification was in accord with the SEM results.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…5. The apparent densities of the major sample was an approximate value of 3.80 g/cm 3 and relative density also has reached more than 95%. It is noticeable that the good degree of densification was in accord with the SEM results.…”
Section: Resultsmentioning
confidence: 91%
“…The peaks of sintered ceramics assigned to the standard data for Pr2Zr3(MoO4)9 (JCPDS No. 52-0688), which indicated that the Pr2Zr3(MoO4)9-like crystal structure with a 3 Rc space group was obtained. According to the result, the composition of the crystal phase is not changed by the content of (Mg1/3Sb2/3) 4+ ions substitution [14].…”
Section: Resultsmentioning
confidence: 92%
See 3 more Smart Citations